Pelvic Floor Dysfunction and Pelvic Surgery in the Elderly : An Integrated Approach - Gordon, David A.; Katlic, Mark R. (Springer New York : Imprint: Springer, 2017)
This text provides a comprehensive, state of the art review of this field and will serve as a resource for urologists, colorectal surgeons, geriatricians, and gynecologists as well as researchers interested in neuromuscular phenomena in the pelvis. The book also reviews new data regarding risk factors for pelvic floor muscle dysfunction and profiles new minimally invasive surgical strategies for well known pelvic disease processes. Each chapter is chock full of data from landmark trials which have been published over the past few years and placed in context with respect to current management techniques for pelvic floor disorders. Written by experts in their field, Pelvic Floor Dysfunction and Pelvic Surgery in the Elderly: An Integrated Approachprovides a concise yet comprehensive summary to help guide patient management.- Resumé vydavatel